Automatic guidance of laparoscope based on the region of interest for robot assisted laparoscopic surgery. (16th December 2016) - Yu, Lingtao; Li, Hongwei; Zhao, Lingyan; Ren, Sixu; Gu, Qing
Abstract: Background: Minimally invasive surgeries rely on laparoscopic camera views to guide the procedure. Traditionally, an expert surgical assistant operates laparoscopic camera. This process is distracting, and the camera is not always placed in an ideal location. To mitigate these problems, we have developed a laparoscopic automatic navigation method. Methods: In this article, a way to determining surgery status based on the distance of surgical instruments is presented. Combining with the surgery status, the region of interest (ROI) in laparoscopic image is defined, and related parameters are given in detail. Comprehensive the above content, the method of laparoscopic automatic navigation based on the ROI is proposed. Results: Finally, introducing the method into a kind of typical minimally invasive laparoscopic surgery robot system (MLSRS), and the method is simulated by using some typical surgical tasks. Conclusion: The results show that this method is feasible.